DETERMINATION OF PEAK GROUND ACCELERATION (PGA) VALUE USING ESTEVA METHOD TO MAP THE PRONE AREAS DUE TO EARTHQUAKES IN WEST SULAWESI - Rahayu, Rifkah
In this study, analysis was conducted on the Peak Ground Acceleration (PGA) value to map the prone areas due to earthquakes in West Sulawesi. This study aims to determine the PGA value and determine the results of mapping prone areas due to earthquakes in West Sulawesi using the Esteva method. Earthquake is a ground-shaking phenomenon caused by the collision between plates, causing the sudden release of energy in the Earth's crust so that it can cause various damage to the Earth's surface. One of the factors that can determine the damage due to earthquake is Peak Ground Acceleration (PGA). PGA is one of the ground acceleration parameters showing the greatest ground acceleration value on the surface that has occurred in an area due to the earthquake. PGA value can be determined by two methods, measurement using accelerograph and calculation using empirical approach methods, such as Esteva method, Donovan, M.C Guirre, and so on. This study used earthquake data that have occurred around West Sulawesi Province from January 1, 1900 – August 31, 2021, with a maximum depth of 70 km and magnitude ? 3. The data was obtained from the United States Geological Survey’s (USGS) earthquake catalog, and the Esteva method was used to calculate the PGA value based on these data. After calculating the PGA values, it was shown that West Sulawesi has PGA values ranging from 45,937 to 431,820 gal, with an intensity of roughly V – VIII MMI, indicating that the majority of its areas are potentially moderate to severe damage. The areas with the greatest risk for earthquake damage were detected in Majene and Polewali Mandar Regencies, specifically around Tammerodo, Sendana, Tubbi Taramanu, and Allu Districts. Meanwhile, regions of North Mamuju Regency, specifically the Lariang and Tikke Raya Districts, have the least risk of damage.